Analisis Pengendalian Kualitas Proses Inspeksi Main Deck Cargo Handling System Pesawat Boeing 747 Varian Kargo Menggunakan Metode PDCA di PT GMF AeroAsia Tbk. - Utomo, Satrio Arif; Utami, Diah (Proceeding Mercu Buana Conference on Industrial Engineering, 2020)
PT GMF AeroAsia is an aircraft maintenance service that specialize in aircraft maintenance and repairs. One of many divisions on PT GMF AeroAsia is Wide Body Base Maintenance Unit that has the scope of maintaining wide body aircraft such as Boeing 747 cargo variants. One of the main highlights of such aircrafts maintenance program is the routine inspection in main deck cargo handling system. One of the problem that often happen is, several defect is often found outside or after inspection phase. This can potentially extend the maintenance time of the aircraft due to later material order. After PDCA analysis is done, it was found that the major contributing factor to that problem is the main deck cargo handling system inspection procedure wasn’t explained specifically in the Aircraft Maintenance Manual, this can increase the potential of late findings to happen during inspection. Another factor that also contributes is the inefficient cleaning method of main deck cargo handling system components that lead to defects covered in debris thus not found during inspection phase. According to pareto chart analysis, it is concluded that unclear inspection instruction contributes to 70 time occurrence (20,2%) from total occurrences and inefficient cleaning methods contributes to 68 time occurrence (19,7%). After a more systematic inspection procedure made, defect within main deck cargo handling system can be found within inspection phase time frame is reduced to only three times within the late finding category.